2011
DOI: 10.1007/s10695-011-9582-0
|View full text |Cite
|
Sign up to set email alerts
|

Impact of silicon-based quantum dots on the antioxidative system in white muscle of Carassius auratus gibelio

Abstract: Silicon-based quantum dots were intraperitoneally injected in individuals of Carassius auratus gibelio. Their effects on white muscle were investigated by following their distribution and impact on the antioxidative system. The GSH level significantly increased after 1 and 3 days of exposure by, respectively, 85.3 and 25.4%. Seven days later, GSH levels were similar to control concentrations. MDA concentration rose after three days by 46.9% and remained at the same level after 7 days. Protein thiol levels sign… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 84 publications
(83 reference statements)
1
6
0
Order By: Relevance
“…Our previous studies on gibel carp revealed the presence of QDs in the liver [42], kidney [43] and even white muscle tissue [44] as early as 24 h post ip. injection.…”
Section: Discussionmentioning
confidence: 95%
“…Our previous studies on gibel carp revealed the presence of QDs in the liver [42], kidney [43] and even white muscle tissue [44] as early as 24 h post ip. injection.…”
Section: Discussionmentioning
confidence: 95%
“…The IP injected QDs were taken up by blood circulation of C. auratus gibelio and spread in tissues such as the white muscle [14] and kidney.…”
Section: Resultsmentioning
confidence: 99%
“…The problem of QD toxicity is controversial and might be overcome by using silicon-based QDs, which seem to have reduced toxicity [14,15]. …”
Section: Introductionmentioning
confidence: 99%
“…The low levels of toxicity produced by SiNCs and their biodegradation are useful for clinical translation [20]. The impact of silicon-based quantum dots on the freshwater fish Carassius auratus gibelio [21][22][23] was also studied recently. The effects of the quantum dots on white muscle, their distribution and their impact on antioxidative stress (GSH) were reported [21].…”
Section: Silicon Nanocrystals (Sincs) and Their Toxicitymentioning
confidence: 99%
“…The impact of silicon-based quantum dots on the freshwater fish Carassius auratus gibelio [21][22][23] was also studied recently. The effects of the quantum dots on white muscle, their distribution and their impact on antioxidative stress (GSH) were reported [21]. However, to the best of our knowledge there has been no study of the toxicity of silicon-based nanocrystals to other marine organisms.…”
Section: Silicon Nanocrystals (Sincs) and Their Toxicitymentioning
confidence: 99%